Meat supply chain in the perspective of UN SDGs - I. V. Djekic (Теория и практика переработки мяса)
This paper presents an overview of the meat supply chain in the perspective of main UN sustainable development goals (SDGs). To perform this overview, meat supply chain was presented with five main stakeholders (livestock farmers, slaughterhouses, meat processors, retailers and consumers). As this chain is specific, four SDGs have been revealed as most important, as follows: SDG6 — Clean water and sanitation; SDG7 — Affordable and clean energy; SDG12 — Sustainable consumption and production; SDG13 — Climate action. Discussion and literature review was performed for each of the four UN SDGs. In addition, other UN SDGs of interest for this supply chain have been briefly presented.